Critical Interculturality as an Alternative to the Dichotomy Between Civic and Ethnic Models of Nation: Reflections from the Case of Ivory Coast - Flan, Goualo Lazare (2025)
This text analyzes how critical interculturality can offer a viable alternative to traditional models of nationhood, which tend to lean towards a civic or ethnic vision. Based on the case of Ivory Coast, it suggests that this perspective can be useful in contexts where civic and ethnic approaches have generated deep identity crises in the management of ethno-cultural diversity. The research, qualitative in nature and based on the case study method, used documental analysis for data collection and analytical induction for information processing. It is concluded that critical interculturality could be key to address, resolve and even prevent conflicts associated with the management of ethnocultural diversity, by fostering a double decolonial turn that decolonizes both being and knowledge. This implies the deconstruction of the coloniality of power and the promotion of a horizontal interconnection between cultures and knowledge, favoring dialogue, respect, equality and harmonious and peaceful coexistence.